Testing the roles of vertical transmission and drought stress in the prevalence of heritable fungal endophytes in annual grass populations - Cavazos, Brittany R. (2018)
Beneficial inherited symbionts are expected to reach high prevalence in host populations, yet many are observed at intermediate prevalence. Theory predicts that a balance of fitness benefits and efficiency of vertical transmission may interact to stabilize intermediate prevalence. We established populations of grass hosts (Lolium multiflorum) that varied in prevalence of a heritable fungal endophyte (Epichloё occultans), allowing us to infer long-term equilibria by tracking change in prevalence over one generation. We manipulated an environmental stressor (elevated precipitation), which we hypothesized would reduce the fitness benefits of symbiosis, and altered the efficiency of vertical transmission by replacing endophyte-positive seeds with endophyte-free seeds. Endophytes and elevated precipitation both increased host fitness, but symbiont effects were not stronger in the drier treatment, suggesting that benefits of symbiosis were unrelated to drought tolerance. Reduced transmission suppressed the inferred equilibrium prevalence from 42.6% to 11.7%. However, elevated precipitation did not modify prevalence, consistent with the result that it did not modify fitness benefits. Our results demonstrate that failed transmission can influence the prevalence of heritable microbes and that intermediate prevalence can be a stable equilibrium due to forces that allow symbionts to increase (fitness benefits) but prevent them from reaching fixation (failed transmission).